2006
DOI: 10.1097/01.wco.0000245369.44199.27
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of inherited neuropathies

Abstract: Animal models have opened up new perspectives on the pathomechanisms and possible treatment strategies of inherited neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 131 publications
(94 reference statements)
1
25
0
Order By: Relevance
“…As indicated by transgenic models of PMP22 overexpression and absence, HNPP results from haploinsufficiency, while CMT1A results from a moderate 2-fold increase in expression; greater than 2-fold overexpression results in DSS. This genotype-phenotype correlation, along with the observation of PMP22-containing protein aggregates in Tr-J mice, supports a mechanism of perturbed intracellular trafficking [76].…”
Section: Models Of Human Diseasesupporting
confidence: 67%
“…As indicated by transgenic models of PMP22 overexpression and absence, HNPP results from haploinsufficiency, while CMT1A results from a moderate 2-fold increase in expression; greater than 2-fold overexpression results in DSS. This genotype-phenotype correlation, along with the observation of PMP22-containing protein aggregates in Tr-J mice, supports a mechanism of perturbed intracellular trafficking [76].…”
Section: Models Of Human Diseasesupporting
confidence: 67%
“…Functional and structural studies could then focus on these areas, with a histological study to confirm the abnormal architecture suggested by the diffusion imaging. Interestingly, several animal models of CMT1A and HNPP have been developed but their CNS has not yet been explored 25. These models might potentially provide insight into the role of PMP22 in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models for the most common subtypes of human CMT disease are now available. They provide clues for understanding the pathogenesis of CMT; they also help to reveal possible treatment strategies for inherited neuropathies [42 ]. The first two therapeutic approaches explained below are nonspecific and directed toward regulating the overall program of myelination.…”
Section: Treatmentmentioning
confidence: 99%